Probing language processing in cochlear implant users with visual word recognition: effects of lexical and orthographic word properties. Issue 2 (1st February 2021) - Amenta, Simona; Artesini, Luca; Musola, Debora; Frau, Giuseppe Nicolò; Vespignani, Francesco; Pavani, Francesco
ABSTRACT: Deaf individuals who learned a spoken language with the aid of a cochlear implant (CI) often experience difficulties with reading. In the present study, we investigate this issue by assessing the impact of lexical and orthographic predictors on visual word recognition in early and late deaf CI-users. Early deaf CI-users were comparable to age-matched hearing controls, for both response accuracy and latencies, whereas late deaf CI-users were slower albeit similarly accurate with respect to age-matched controls. Analyses of the impact of lexical and orthographic predictors, however, revealed that early deaf-CI users were slower than controls in recognising low frequency words and words with high proportion of consonants. In conclusion, early deaf individuals who developed their language using a CI show qualitative differences in visual word processing, above and beyond the overall performance. This suggests that typical overall performance may emerge also in the context of atypical lexical and word form representations.